Association between posterior teeth occlusion and functional dependence among older adults in nursing homes in Japan. Issue 4 (27th April 2016) - Takeuchi, Kenji; Izumi, Maya; Furuta, Michiko; Takeshita, Toru; Shibata, Yukie; Kageyama, Shinya; Ganaha, Seijun; Yamashita, Yoshihisa
Abstract : Aim: To examine whether posterior teeth occlusion is associated with functional dependence regardless of the number of natural teeth among Japanese nursing home residents. Methods: The present cross‐sectional study included 234 residents aged >60 years from eight nursing homes in Aso City, Japan. Functional dependence in basic activities of daily living was measured using the Barthel Index, and the primary outcome was independence for essential personal care (Barthel Index ≥ 60 points). Posterior teeth occlusion was assessed by a dentist using the total number of functional tooth units, depending on the number and location of the remaining natural and artificial teeth on implant‐supported, fixed, and removable prostheses. Logistic regression models were used to assess univariate and multivariate associations between the total number of functional tooth units and independence for essential personal care. Models were sequentially adjusted for the number of natural teeth, demographic characteristics, socioeconomic status, health behaviors and comorbidities. Results: Independence for essential personal care was found in 14.1% of participants. Greater total numbers of functional tooth units were significantly associated with greater odds of independence for essential personal care (odds ratio 1.12; 95% confidence interval 1.01–1.24). The association remained significant after adjustment for the number of natural teeth and other possible confounders (odds ratio 1.14, 95% confidence interval 1.01–1.29). Conclusions: Posterior teeth occlusion was independently associated with functional dependence among nursing home older residents in Japan. The maintenance and restoration of posterior teeth occlusion might be preventive factors against late‐life functional decline.Geriatr Gerontol Int 2017; 17: 622–627 .